WADAH DARI TEMPURUNG KELAPA DI DALAM PERAHU PUNJULHARJO - Hari Lelono (Balai Arkeologi Yogyakarta, 2011)
Container is one of man’s living tools which has a function where everything hard or soft, fluid or certain seeds will be placed. Based on its function, container uses spesific materials like clay, leaves and fruits which have big and strong seeds. In ancient Punjulharjo ship located in Kabupaten Rembang, Central Java, it was found a container made of coconut shell. In the livinghood of some ancient traditional communities, the containers are still used to spport their daily activities. This fact could reveal the time when it had been by the ancestors.